2024
DOI: 10.21203/rs.3.rs-3915320/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Antibodies Targeting the CCHFV Nucleocapsid Protein Require TRIM21 for Protection

David Hawman,
Shanna Leventhal,
Kimberly Meade-White
et al.

Abstract: Crimean-Congo Hemorrhagic Fever Virus (CCHFV) is a negative-sense RNA virus spread by Hyalomma genus ticks across Europe, Asia, and Africa. CCHF disease begins as a non-specific febrile illness which may progress into a severe hemorrhagic disease and there are currently no widely approved or highly efficacious interventions available. Recently, we reported a self-replicating, alphavirus-based RNA vaccine which expresses the CCHFV nucleoprotein and is protective against lethal CCHFV disease in mice. This vaccin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…3c). As we have previously shown that humoral immunity is the primary correlate of protection 5,22,23 , we hypothesized that antibody titer would correlate with viral loads. Indeed, we found that CCHFV-specific antibody titer significantly and inversely correlated with viral load in multiple tissues, including the heart, liver, kidney, and adrenal gland (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3c). As we have previously shown that humoral immunity is the primary correlate of protection 5,22,23 , we hypothesized that antibody titer would correlate with viral loads. Indeed, we found that CCHFV-specific antibody titer significantly and inversely correlated with viral load in multiple tissues, including the heart, liver, kidney, and adrenal gland (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…CCHFV has substantial genetic diversity, differing by >5% in the NP and over 25% in the GPC 38 , and thus, an effective vaccine will need to protect against diverse strains of CCHFV. We have shown in mice that our repNP vaccine and passive transfer of NPimmune serum can protect against a highly divergent strain of CCHFV 5,22,23 , making the more conserved NP a promising vaccine-encoded antigen. Fourthly, we did not evaluate the durability of immune responses to CCHFV following repRNA vaccination.…”
Section: Discussionmentioning
confidence: 98%